2009
DOI: 10.1021/bm9000298
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected In Vivo Anti-Inflammatory Activity Observed for Simple, Surface Functionalized Poly(amidoamine) Dendrimers

Abstract: We report unexpected anti-inflammatory properties for naked, unmodified poly(amidoamine) (PAMAM) dendrimers bearing simple surface functionality (e.g., -NH(2), -OH, etc.). This property was discovered serendipitously while studying the drug delivery features of PAMAM dendrimer-indomethacin complexes. Activity was quantitated by using three independently recognized in vivo anti-inflammatory assay methods, namely, (1) the carrageenan-induced paw edema model (acute activity), (2) the cotton pellet test, and (3) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 29 publications
7
139
1
Order By: Relevance
“…In this section, we summarize not only the antiinflammatory role of dendrimers displayed towards immune cells derived from myeloid lineage (such as monocyte-derived macrophages (MDMs), and immature dendritic cells) (Shaunak et al, 2004), peripheral blood monocytes (Fruchon et al, 2009) and peritoneal macrophages (Chauhan et al, 2009), but also towards the extravasation of inflammatory effectors (leukocytes) at the site of inflammation (Ulbrich et al, 2003), anti-HIV activity, anti-arthritis effect and inhibition of iNOS and COX-2 enzymes etc.…”
Section: Dendrimers As Anti-inflammatory Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we summarize not only the antiinflammatory role of dendrimers displayed towards immune cells derived from myeloid lineage (such as monocyte-derived macrophages (MDMs), and immature dendritic cells) (Shaunak et al, 2004), peripheral blood monocytes (Fruchon et al, 2009) and peritoneal macrophages (Chauhan et al, 2009), but also towards the extravasation of inflammatory effectors (leukocytes) at the site of inflammation (Ulbrich et al, 2003), anti-HIV activity, anti-arthritis effect and inhibition of iNOS and COX-2 enzymes etc.…”
Section: Dendrimers As Anti-inflammatory Agentsmentioning
confidence: 99%
“…In a recent study, PAMAM dendrimers with terminal-NH 2 (G4-NH 2 ), -OH (G4-OH) and -COOH (G4.5-CO 2 H) (Chauhan et al, 2009) were used for the in vitro analysis of LPS-induced nitric oxide (NO) and cyclo-oxygenase 2 (COX-2) activity in rat peritoneal macrophages. G4-NH 2 and G4-OH dendrimers showed maximum inhibitory activity as compared to G4.5-CO 2 H. In another study, the aminoethylethanolamine-capped dendrimers (G4-AEEA) and hydroxyl terminated dendrimers (G4-OH) displayed highest inhibitory activity of COX-2.…”
Section: Proinflammatory Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…10−12 Surprisingly, PAMAM dendrimers without any drug payload have also been shown to exhibit antiinflammatory properties, particularly generation 4 (G4) PAMAM dendrimers. 12 It was suggested that the inhibition of COX-2 activity may explain some of the anti-inflammatory effects, although the specific mechanism(s) of G4 PAMAM action remain unclear. 12 In addition, G3 dendritic polyglycerol sulfates (dPGS) also possess anti-inflammatory properties, though through a completely different mechanism of action.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 It was suggested that the inhibition of COX-2 activity may explain some of the anti-inflammatory effects, although the specific mechanism(s) of G4 PAMAM action remain unclear. 12 In addition, G3 dendritic polyglycerol sulfates (dPGS) also possess anti-inflammatory properties, though through a completely different mechanism of action. 13 It is believed that dPGS dendrimers may function as macromolecular inhibitors, through direct interactions with complement factors, essential mediators of the innate immune response.…”
Section: ■ Introductionmentioning
confidence: 99%